Pembinaan Kelompok Bina Keluarga Balita (BKB) di Desa Sumberagung Kecamatan Batanghari Kabupaten Lampung Timur - Kholifatul Munawaroh; Fitri Wahyuni; Pindo Riski Saputra (Fakultas Ilmu Sosial dan ilmu Politik, 2022)
Skills to educate, nurture, and monitor children's growth and development are important for every parent to have to meet the needs of children, namely the needs of hone, love and nurture so that children can grow and develop optimally. Bina Keluarga Balita (BKB) is a government program that aims to improve the knowledge and skills of parents and other family members in fostering the growth and development of toddlers through physical, motor intelligence, emotional and socioeconomic stimuli as well as possible through the interaction of parents and toddlers in order to achieve optimal growth and development. The realization of the involvement of community members in encouraging BKB cadres to consistently carry out coaching every month in Sumberagung Village, in Batang Hari District, in East Lampung Regency. The target of this service location is BKB Cadres and the community, in Sumberagung Village. Activities will be carried out in the form of training through film screenings, lectures and diccusion activities. The success of this activity is evaluated through pre- and post-test activities. Quantitatively, the average value of participants before the activity was 50 and increased to 73.25 after the training activity was carried out. The average increase was 23.25 points. Both the highest pre-test and post-test scores are 90 and the lowest score is 50.